Successful treatment of refractory listeria meningitis and bacteremia with trimethoprim-sulfamethoxazole in an immunocompetent child - Polat, Meltem; Kara, Soner Sertan; Tapısız, Anıl; Derinöz, Okşan; Çağlar, Kayhan; Tezer, Hasan (The Turkish Journal of Pediatrics, 2016)
Listeria monocytogenes is an important cause of life-threatening bacteremia and meningoencephalitis in neonates, pregnant women, the elderly, and immunocompromised individuals. However, it is an uncommon cause of illness in immunocompetent children beyond the neonatal period. Ampicillin with or without an aminoglycoside remains the best treatment for listeriosis. Here, we report a rare case of Listeria meningitis and bacteremia in a 7-month-old immunocompetent girl, which was refractory to ampicillin plus gentamicin treatment and successfully treated by the addition of TMP/SMX.